Diverging shifts in spring phenology in response to biodiversity loss in a subtropical forest. (14th September 2019) - Du, Yanjun; Yang, Bo; Chen, Si‐Chong; Ma, Keping
Abstract: Questions: Despite our increased understanding of how climate change influences plant phenology, it remains poorly understood whether diversity loss could alter phenology as well. Here we investigated the following: (a) do changes in plant diversity affect leaf‐out and flowering dates for woody species; (b) which group of variables are more important in influencing leaf‐out and flowering dates, abiotic variables (soil variables) or biotic variables (plant diversity)? Study site: A subtropical forest in the Biodiversity–Ecosystem Functioning Experiment of China, located in Jiangxi Province, China. Methods: Species were planted in various combinations to create plots with varying tree richness: 1, 2, 4, 8, 16 or 24 species. We monitored leaf‐out and flowering dates of eight randomly selected species in 17 plots in 2018. A linear model was used to test whether species diversity was a predictor of leaf‐out/flowering times for each species. We then fit linear mixed‐effects models to assess the combined influence of species diversity, soil Total Carbon and Total Nitrogen on the overall community. Results: In the low‐diversity plots, we found two species leafing out earlier, one leafing out later and four showing no significant difference. Leaf‐out date advanced an average of 0.3 days per species lost. Of all the biotic and abiotic predictor variables, Total Nitrogen was the only one significantly correlated with leaf‐out date. No significant correlation was found between species diversity and flowering date for any of the species. Conclusions: Our study provides the first empirical evidence concerning the effects of biodiversity loss on plant spring phenology for woody species. Our findings illustrate that fluctuation in plant diversity could alter the timing of leaf‐out and that abiotic variables may be more important than biotic variables in determining leaf‐out dates in subtropical forest. Overall, declining diversity may exacerbate the phenological changes attributed to rising global temperatures. Abstract : We investigated whether phenology shifts in response to biodiversity loss in a subtropical forest, and we found diverging shifts in spring phenology, with leaf‐out date advancing an average of 0.3 days per species lost. Our findings indicate that declines in diversity could further exacerbate the phenological changes attributed to rising global temperatures.